Enhancing Work Capability, Leadership Style, and Work Motivation for Improved Internationalization Performance of SMEs: A Case Study in the Micro Sector of Worm and Laboratory Animal Production in Indonesia - Suryo P, R. Agung; Sudarmiatin; Bidin, Rosmiza (Asian Journal of Management Analytics, 2024)
This study investigates the influence of work capability, leadership style, and work motivation on the performance of Micro, Small, and Medium Enterprises (MSMEs) in the context of internationalization. The method of analysis used is path analysis to test the relationships between variables. The research sample of 135 respondents was chosen to consist of employees working in the industry of breeding worms, rats, and animals for medical purposes in Indonesia. Data were collected through questionnaires distributed to respondents. The results of path analysis indicate a significant positive influence of work capability, leadership style, and work motivation on the performance of MSMEs in the context of internationalization. The implications of these findings underscore the importance of developing work capability, implementing effective leadership styles, and enhancing work motivation to improve the performance of MSMEs in facing the challenges of internationalization.